Qualitative research in the sociolinguistics of contact in Romance languages: systemic evidence, anthropological evidence - Jablonka, Frank (Romanica Olomucensia, 2015)
The present article considers the divergences between quantitative and qualitative field approaches, especially on the basis of examples of empirical studies in variational sociolinguistics in contact situations in the Aosta Valley and in Morocco. One of the critical points is the question of representativity. Contrary to quantitative research, qualitative approaches are not interested in numerical but in exemplary representativity. From the viewpoint of the anthropology of communication, it is possible to integrate the "macro" into the "micro" perspective. This research strategy converges with the paradigm of complexity adapted to sociolinguistics, with the focus on holism and recursivity.
Keywords: anthropology of communication; complexity; representativity; field research.